COMMUNICATION PERSPECTIVES OF NRHM: A STUDY ON THE PERCEPTIONS OF TRIBAL POPULATION - Amit Kumar Singh; Dr. Rahul Amin (Revista Electronica de Veterinaria, 2024)
This study explores the communication perspectives of the National Rural Health Mission (NRHM) among tribal populations, focusing on their perceptions and experiences with healthcare delivery. Conducted in the rural areas of Ranchi, the research aims to identify  the communication aspect of NRHM and to find out the authentic source and best  centre of information regarding health using quantitative approach, the study incorporates structured surveys with a purposive sample of 600 participants. Key findings reveal significant challenges in communication, particularly related to Accredited Social Health Activists (ASHAs) and Auxiliary Nurse Midwives (ANMs), which often result in limited awareness and understanding of healthcare programs. The study underscores the need for improved communication strategies to bridge gaps, enhance healthcare outcomes, and elevate patient satisfaction within tribal communities.